Dampak Subsidi Pupuk Terhadap Petani Kecamatan Simpur Kabupaten Hulu Sungai Selatan - Lestari, Maulina Ayu; Lina Suherty; Chairul Sa’roni (PPJP ULM, 2020)
This research was conducted to analyze (1) How is the role of fertilizer subsidies inincreasing farmer production ; (2) Is there a difference in income for farmers before usingsubsidized fertilizers.The research respondents were 72 farmers in Simpur, Hulu Sungai Selatan, which can beused in the data processing. Data were processed using Paired Sample T-test using SPSSapplication version 26.This study indicates that the measurement of the implementation of fertilizer subsidydistribution is instrumental because it can increase farmers 'incomes so that farmers' lives aremore prosperous. Also, the existence of fertilizer subsidies has dramatically helped farmers inSimpur District, Hulu Sungai Selatan, to increase agricultural commodities production tosupport national food security. The income of farmers who before using fertilizer subsidies lookssignificantly different.